Comparison of Performance of 1D5P with 2 Input and 1 Input Model in Forecasting of Power Output for Photovoltaic Systems - Dawan, Promphak; Kittisontirak, Songkiate; Sriprapha, Kobsak; Muanglua, Rangson; Titiroongruang, Wisut; Niemcharoen, Surasak (My University, 2018)
This paper presents the comparison on forecasting performance of power output for photovoltaic system type 1D \pmb{5}\mathbf{P}, which used 1 input parameter being solar irradiance and 2 input parameters consisting of solar irradiance and the temperature model. The result shows that the forecasting of power output for photovoltaic system type 1D5P, which used 1 input parameter, provided root-mean-square deviation (RMSE) at 0.04 and for 2 input parameters provided RMSE at 0.05.
Keywords: 1D5P Model; Module Temperature; Power Output; RMSE; Solar Irradiance